2001
DOI: 10.1128/iai.69.12.7866-7872.2001
|View full text |Cite
|
Sign up to set email alerts
|

How Giardia Swim and Divide

Abstract: To determine how binuclear giardia swim, we used video microscopy to observe trophozoites of Giardia intestinalis, which were labeled with an amino-specific Alexa Fluor dye that highlighted the flagella and adherence disc. Giardia swam forward by means of the synchronous beating of anterior, posterolateral, and ventral flagella in the plane of the ventral disc, while caudal flagella swam in a plane perpendicular to the disc. Giardia turned in the plane of the disc by means of a rudder-like motion of its tail, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 22 publications
9
65
2
Order By: Relevance
“…This model of cell division can explain prior studies on nuclear partitioning during cytokinesis, albeit with an alternative mode of cytokinesis than that originally proposed (Ghosh et al, 2001).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…This model of cell division can explain prior studies on nuclear partitioning during cytokinesis, albeit with an alternative mode of cytokinesis than that originally proposed (Ghosh et al, 2001).…”
Section: Introductionsupporting
confidence: 57%
“…To determine the pattern of nuclear partitioning and inheritance, we used fluorescence in situ hybridization (FISH) to visualize an episomal plasmid in the cenH3::GFP strain, which is maintained by one nucleus in each Giardia trophozoite (Ghosh et al, 2001;Singer et al, 1998;Yu et al, 2002). In each cell, we observed the episomal plasmid FISH signal in only one nucleus (either the left or the right) as previously reported (Ghosh et al, 2001).…”
Section: Patterns Of Nuclear Inheritance Using Fish Of An Episomal Plmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous reports on Giardia mitosis stated conclusions based only in light microscopic observations (Filice, 1952;Cerva and Nohýnk-ová, 1992;Kabnick and Peattie, 1990;Nohýnková et al, 2000;Ghosh et al, 2001, Yu et al, 2002. The following suggestions have been made: (1) mitosis in Giardia corresponds to a semi-open orthomitosis (Nohýnková et al, 2000); (2) during mitosis the nuclear envelope is perforated in a sieve-like manner in both nuclei (Nohýnková et al, 2000); (3) spindle microtubules enter the nucleus through tiny holes (Nohýnková et al, 2000); (4) pairs of nuclei are tethered together by microtubules which surround the nuclei (Ghosh et al, 2001). However, all these proposals were not supported by any electron microscopic observation.…”
Section: Introductionmentioning
confidence: 99%
“…Most ultrastructural studies have focused on the cytoskeleton and adhesive disc of Giardia (reviewed in Gillin et al, 1996;Adam, 2001). Some studies have shown that the disc is fragmented at some stages of the Giardia cell cycle, such as during cell division (Ghosh et al, 2001) and encystation (Sheffield and Bjorvatn, 1977). However, careful study of each step of the Giardia cell cycle has not been carried out.…”
Section: Introductionmentioning
confidence: 99%